Diastematomyelia differences in management of diastemetomyelia with associated abnormalities versus isolated diastemetomyelia: a case series - P., Salini Raani J.; Rao, Ashwin; Balu, Madhan; Rao, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Diastematomyelia (DM), also known as split cord malformation (SCM) is a type of spinal dysraphism. It is a very rare congenital spinal anomaly characterized by clefting of the spinal cord due to a partial or complete bony or fibrous septum within the spinal canal with splaying of the posterior spinal elements resulting in localized division of the spinal cord into two parts on either side of the septum which typically reunite below the cleft. The pathology was first described by Cruvelhier in 1853. About 1-3 per 1000 live birth, is the estimated incidence of spinal dysraphism and neural tube defects (NTD) occurs more commonly in females (55-70%). Prenatal diagnosis of DM is possible by ultrasonography (USG). The clinical significance of DM is that it may manifest as an isolated abnormality or in association with other spinal abnormalities such as spina bifida, Arnold-Chiari malformation, hemivertebra, butterfly vertebra, kyphoscoliosis or part of Jarcho-Levin syndrome. The management of pregnancy with a foetus diagnosed with DM antenatally, differs based on whether the foetus has an isolated DM with intact skin or DM with more serious associated anomalies. We present two cases of Foetal DM both diagnosed by antenatal USG, Case 1 was diagnosed at 16 weeks gestation age (GA) with DM associated with Type II Arnold-Chiari malformation, hydrocephalus and case 2 was diagnosed with isolated DM at 19 weeks 2 days GA.